LENGTH-WEIGHT RELATIONSHIP AND HARVESTABLE SIZE OF LABEO CALBASU FROM JAWAHAR SAGAR DAM OF SOUTHERN RAJASTHAN, INDIA - SARANG, N.; SHARMA, L. L. (Journal of the Inland Fisheries Society of India, 2022)
Length-weight relationship and harvestable size of Labeo calbasu from Jawahar Sagar dam (24o82.792 N latitude and 76052.072 E longitude) of southern Rajasthan was studied using key scales. The length-weight relationship of this fish was observed to conform to the formula Log W = - 3.34124 +1.91260 Log TL. The coefficient of correlation (r) 0.959 showed a high degree of correlation between total length and weight. Maximum three annual rings were found in the cycloid scales of fish to assess growth data in the samples representing 1 to 4 year classes. On the basis of growth parameter the harvestable size of 60 cm at the age of 3+ year class has been calculated for Labeo calbasu of Jawahar Sagar dam. Key words : Length-weight relationship, growth parameters, harvestable size, Labeo calbasu and Jawahar Sagar dam.